\(B=\left(\sqrt{x}-4\sqrt{x}+1\right)\left(\sqrt{x}+4\sqrt{x}\right)\left(x-\sqr...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

11 tháng 7 2015

\(B=\left(-3\sqrt{x}+1\right).5\sqrt{x}.\left(x-\sqrt{x}+1\right)=5\sqrt{x}.\left(-3x\sqrt{x}+3x-3\sqrt{x}+x-\sqrt{x}+1\right)\)

\(=5\sqrt{x}\left(-3x\sqrt{x}+4x-4\sqrt{x}+1\right)=-15x^2+20x\sqrt{x}-20x+5\sqrt{x}\)

15 tháng 9 2020

\(M=\frac{\sqrt{x-\sqrt{4\left(x-1\right)}}+\sqrt{x+\sqrt{4\left(x-1\right)}}}{\sqrt{x^2-4\left(x-1\right)}}\cdot\left(1-\frac{1}{x-1}\right)\)

\(M=\frac{\sqrt{x-1-2\sqrt{x-1}+1}+\sqrt{x-1+2\sqrt{x-1}+1}}{\sqrt{x^2-4x+4}}\cdot\frac{x-1-1}{x-1}\)

\(M=\frac{\sqrt{\left(\sqrt{x-1}-1\right)^2}+\sqrt{\left(\sqrt{x-1}+1\right)^2}}{\sqrt{\left(x-2\right)^2}}\cdot\frac{x-2}{x-1}\) (đk: \(x\ge1\)

\(M=\frac{\left|\sqrt{x-1}-1\right|+\left|\sqrt{x-1}+1\right|}{\left|x-2\right|}\cdot\frac{x-2}{x-1}\)

Nếu \(1\le x< 2\) =>\(M=\frac{1-\sqrt{x-1}+\sqrt{x-1}+1}{2-x}\cdot\frac{x-2}{x-1}\)

\(M=-\frac{2}{x-1}\)

Nếu x > 2 => \(M=\frac{\sqrt{x-1}-1+\sqrt{x-1}+1}{x-2}\cdot\frac{x-2}{x-1}\)

\(\frac{2\sqrt{x-1}}{x-1}=\frac{2}{\sqrt{x-1}}\)

1 tháng 10 2020

A = \(\frac{2}{\sqrt{x-1}}\)

25 tháng 6 2017

a)\(\left(1-\sqrt{x}\right)\left(1+\sqrt{x}+x\right)=1-\sqrt{x^3}\)

b) \(\left(\sqrt{x}+2\right)\left(x-2\sqrt{x}+4\right)=\sqrt{x^3}+8\)

c)\(\left(\sqrt{x}-\sqrt{y}\right)\left(x+y+\sqrt{xy}\right)=\sqrt{x^3}-\sqrt{y^3}\)

d)\(\left(x+\sqrt{y}\right)\left(x^2+y-x\sqrt{y}\right)=x^3+\sqrt{y^3}\)

21 tháng 7 2018

a. =\(\frac{x\sqrt{xy}+y\sqrt{x^2}-x\sqrt{y^2}-y\sqrt{xy}}{\sqrt{xy}}\)=\(\frac{x\sqrt{xy}+xy-xy-y\sqrt{xy}}{\sqrt{xy}}\)
=\(\frac{x\sqrt{xy}-y\sqrt{xy}}{\sqrt{xy}}\)=\(\frac{\sqrt{xy}\left(x-y\right)}{\sqrt{xy}}\)=\(x-y\)
b. =\(\frac{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}{\sqrt{x-1}}\)=\(x+\sqrt{x}+1\)